2009
DOI: 10.1111/j.1365-2745.2009.01580.x
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation in the conceptual melting pot

Abstract: Summary 1. Here we present an introduction to this issue’s Special Feature arising from the British Ecological Society Symposium: Facilitation in Plant Communities (20–22 April 2009). 2. Papers in the Special Feature demonstrate the benefits that arise from cross‐system application of general concepts, for example, the well‐known stress gradient hypothesis. Such comparisons challenge our definition of facilitation, as well as our pre‐conceptions on the nature of intermediary organisms. 3. We suggest that un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 20 publications
1
44
0
Order By: Relevance
“…We provide compelling experimental evidence demonstrating that exclusion of negative ecosystem-engineering interactions may be useful in initiating the reestablishment of those species whose initial establishment is hampered by thresholds but who subsequently benefit from selffacilitating positive feedbacks. Present findings underline that in addition to the recent growing awareness of the need to consider positive (facilitating) interactions in ecological theory (i.e., Bruno et al 2003, Brooker andCallaway 2009) and ecological conservation and restoration projects (Byers et al 2006, Crain and Bertness 2006, Halpern et al 2007, van Katwijk et al 2009, it is equally important to also consider negative engineering interactions between ecosystem-engineering species in restoration projects. This result reemphasizes and (by specifically focusing on negative engineering interactions) extends a wealth of older theory (Rhoads et al 1970, Peterson 1980, Reise 1985, Wilson 1991.…”
Section: Discussionmentioning
confidence: 62%
“…We provide compelling experimental evidence demonstrating that exclusion of negative ecosystem-engineering interactions may be useful in initiating the reestablishment of those species whose initial establishment is hampered by thresholds but who subsequently benefit from selffacilitating positive feedbacks. Present findings underline that in addition to the recent growing awareness of the need to consider positive (facilitating) interactions in ecological theory (i.e., Bruno et al 2003, Brooker andCallaway 2009) and ecological conservation and restoration projects (Byers et al 2006, Crain and Bertness 2006, Halpern et al 2007, van Katwijk et al 2009, it is equally important to also consider negative engineering interactions between ecosystem-engineering species in restoration projects. This result reemphasizes and (by specifically focusing on negative engineering interactions) extends a wealth of older theory (Rhoads et al 1970, Peterson 1980, Reise 1985, Wilson 1991.…”
Section: Discussionmentioning
confidence: 62%
“…The relative importance of these transfer pathways, nevertheless, remains debated (Robinson and Fitter 1999;Simard and Durall 2004;Philip and others 2010). If, in fact, net C transfer through EM networks is common, then traditional models of plant community dynamics (for example , Tilman 1988) need modification to allow for a multiplicity of interactions among plants, rather than simply competition determined by resource ratios (Simard and others 1997a, b;Read 2002;Brooker and Callaway 2009;van der Heijden and Horton 2009). Plant-to-plant facilitation has been shown to be most important when environmental stress is high, as predicted by the stress-gradient hypothesis (Greenlee and Callaway 1996;Callaway and others 2002;Castro and others 2004;Liancourt and others 2005;Cavieres and others 2006), and EM networks may play a role in this facilitation through either interplant transfer of nutrients or water, or through mycorrhizal fungal colonization of establishing plants others 2002, 2005;Querejeta and others 2003;Nara 2006;Egerton-Warburton et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This decrease in diversity is prevented, however, if rare species have a higher survival rate and/or recruitment rate than that of abundant species. The JanzenConnell model (Janzen 1970, Connell 1971, niche complementarity hypothesis (Shelly 1985, Hector et al 1999) and facilitation hypothesis (Bruno et al 2003, Brooker et al 2008, Brooker and Callaway 2009) predict such frequency-dependent mortality and recruitment. Janzen (1970) and Connell (1971) suggested that the mortality of seeds and/or seedlings is frequency dependent due to the frequency dependence of interactions between hosts and specialized pathogens, herbivores or predators.…”
Section: Introductionmentioning
confidence: 99%
“…Because locally abundant species are subjected to more conspecific competition, they are at a relative disadvantage. In the process of facilitation (Bruno et al 2003, Brooker andCallaway 2009), an individual benefits nearby individuals of other species. Recent studies have demonstrated strong effects of facilitation on individual fitness, population distributions and growth rates (Callaway 1995, Bertness and Leonard 1997, Jones et al 1997, Stachowicz 2001.…”
Section: Introductionmentioning
confidence: 99%